Are you a hungry monster? - Karsten, Guilherme (Karsten, Guilherme. Your Scary Monster Friend., 2025)
Hello, monster friend! I have a monstrous snack for you! Can you smell it? It is so yummy (disgusting?). ! Open the book and share a feast with me.